The emerging role of glucagon-like peptide-1 receptor agonists in male infertility: mechanisms, experimental evidence, and future clinical perspectives - Shubham Biswas; Fatima Rani; Kaustubh Bhardwaj; Chhandak Bera; Sneha Yadav (International Journal of Basic & Clinical Pharmacology, 2026)
Obesity and metabolic dysfunction are major modifiable risk factors for male infertility, affecting reproductive function via insulin resistance, oxidative stress, chronic inflammation, hypothalamic-pituitary-gonadal axis dysregulation and impaired steroidogenesis. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are commonly used to treat obesity and type 2 diabetes mellitus and have emerged as potential modulators of male reproductive health, due to their metabolic effects and potential direct effects on reproductive tissues. This narrative review aimed to assess the current evidence regarding the potential role of GLP-1RAs in obesity-related male infertility, including underlying mechanisms, experimental findings, clinical evidence, and future therapeutic implications. A narrative literature search was conducted in PubMed, Scopus, Google Scholar, and Web of Science for relevant publications from 2018 to 2025, including original research, clinical trials, observational studies, experimental studies, systematic reviews, and relevant guidelines on GLP-1RAs, male reproductive physiology, semen parameters, reproductive hormones, and obesity-associated infertility. Evidence suggests that GLP-1RAs may influence male reproductive function via both indirect and direct effects on reproductive tissues. Experimental studies have shown expression of the GLP-1 receptor in reproductive cells including Leydig cells, Sertoli cells and spermatozoa, suggesting potential roles in steroidogenesis, cellular metabolism, mitochondrial function and spermatogenesis. In addition, the relative contribution of direct pharmacological effects compared to metabolic improvement by weight loss remains unclear. Overall, GLP-1RAs appear to be a promising therapeutic approach for treating obesity-related male reproductive dysfunction by acting on both metabolic health and possibly restoring reproductive function. However, there is not enough evidence at present to justify the recommendation of GLP-1RAs as established fertility-enhancing agents. To determine their role in the evidence-based management of male infertility, large, adequately powered randomised controlled trials evaluating semen quality, sperm DNA integrity, reproductive hormone profiles, pregnancy, and long-term safety are required.